127k views
2 votes
6 = 2 - 2x + 10

X=??

2 Answers

4 votes
X= 3

When you combine terms you end with:
6=12-2x
-6 = - 2x (12 was subtracted from both sides)
Then you divide both sides by -2 and end up with 3 = x
User Akhil Ghatiki
by
4.7k points
0 votes

Answer:

x=3

Explanation:

6 = 2 - 2x + 10

Subract 2 from both sides: 4= -2x + 10

Subtract 10 from both sides: -6=-2x

Divide both sides by -2: 3=x

x=3

User Naeem Ul Wahhab
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.